Socioeconomic status and morbidity pattern among the elderly population in Bankura district, West Bengal - Ujjwal Das; Nishamani Kar (BLDE University Journal of Health Sciences)
BACKGROUND: The geriatric population is increasing in India as well as in the world. Prevailing of different types of morbidity among the geriatric population is an important health challenge for most developing countries. Thus present study examines the socioeconomic status and morbidity pattern among elderly individuals in Bankura district, West Bengal. DATA AND METHODS: A total of 465 elderly from rural areas of Bankura district, West Bengal, were selected by systematic random sampling. A pretested, semi-structured questionnaire was administered to collect data. Blood pressure, height, and weight were measured and recorded. Ethical clearance was obtained and informed consent was taken from study participants. Multivariate logistic regression was used to evaluate the risk factors of morbidity. RESULTS: The overall prevalence of morbidity among the study participants was 82.7%. The majority of the study population suffers from hypertension (71.8%), followed by diabetes (33.2%), heart disease (21.5%), and depression (15.1%). The prevalence of hypertension among males was 70.2 (150) and in female subjects was 73.3 (156). Multivariate logistic regression implied that individuals older than 65 years higher risk of morbidity as compared to older adults 55 years of age. The result also suggested that no education, widowed, not physically working, and lifestyle indicators such as smoking, tobacco use, and excess alcohol intake were the significant risks for multi-morbidity. The overall risk of morbidity was higher among the females than the male counterparts. CONCLUSION: This study underscored significant health issues affecting the elderly population. Hypertension was found to have the highest burden of morbidity, followed by bone diseases such as osteoporosis and osteoarthritis. Therefore, enhancing geriatric health services is urgently needed to improve their quality of life.